AMPA Receptors: A Key Piece in the Puzzle of Memory Retrieval - Pereyra, Magdalena; Medina, Jorge H. (Frontiers in Human Neuroscience, 2021)
Retrieval constitutes a highly regulated and dynamic phase in memory processing. Its rapid temporal scales require a coordinated molecular chain of events at the synaptic level that support transient memory trace reactivation. AMPA receptors (AMPAR) drive the majority of excitatory transmission in the brain and its dynamic features match the singular fast timescales of memory retrieval. Here we provide a review on AMPAR contribution to memory retrieval regarding its dynamic movements along the synaptic compartments, its changes in receptor number and subunit composition that take place in activity dependent processes associated with retrieval. We highlight on the differential regulations exerted by AMPAR subunits in plasticity processes and its impact on memory recall.